2010
DOI: 10.1242/jcs.065326
|View full text |Cite
|
Sign up to set email alerts
|

Cross-regulation of cytokine signalling: pro-inflammatory cytokines restrict IL-6 signalling through receptor internalisation and degradation

Abstract: The inflammatory response involves a complex interplay of different cytokines which act in an auto- or paracrine manner to induce the so-called acute phase response. Cytokines are known to crosstalk on multiple levels, for instance by regulating the mRNA stability of targeted cytokines through activation of the p38-MAPK pathway. In our study we discovered a new mechanism that answers the long-standing question how pro-inflammatory cytokines and environmental stress restrict immediate signalling of interleukin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
62
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 52 publications
5
62
0
Order By: Relevance
“…The role of phospho-S782 in gp130 was first documented in 2000 to downregulate gp130 cell surface expression (5). Recently, it has been reported that phospho-S782-associated downregulation of gp130 cell surface expression is mediated by immediate internalization (46). Indeed, phosphorylation of many transmembrane receptors at Ser/Thr residues is commonly associated with the negative modulation of receptor activity (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of phospho-S782 in gp130 was first documented in 2000 to downregulate gp130 cell surface expression (5). Recently, it has been reported that phospho-S782-associated downregulation of gp130 cell surface expression is mediated by immediate internalization (46). Indeed, phosphorylation of many transmembrane receptors at Ser/Thr residues is commonly associated with the negative modulation of receptor activity (47).…”
Section: Discussionmentioning
confidence: 99%
“…8). SC144 binding induces conformational changes and activity loss in the cell surface-bound gp130 receptor, exposing the Ser782 residue to protein kinases such as CaMKII, CaMKIV, and MK2 (6,46). The decrease in gp130 activity leads to the inactivation of downstream signaling pathways involving Stat3 and Akt.…”
Section: Discussionmentioning
confidence: 99%
“…Stress-induced p38 MAPK has been highlighted as a key player in previous studies investigating the cross-talk regulation of IL-6 signaling (8,10,18,37). Furthermore, p38 plays a crucial role in the induction and maintenance of chronic inflammation and is strongly activated in inflammatory arthritis (38).…”
Section: Discussionmentioning
confidence: 99%
“…In hepatocytes, the internalization of gp130 in response to p38-inducing stimuli was found to require phosphorylation of serine residue 782 in the cytoplasmic tail, which is proximal to the di-leucine internalization motif (10). In primary monocytes, stimulation with IL-1␤ promoted the phosphorylation of gp130 serine 782 ( Figure 6A), indicating that this residue may act as a stress sensor not only in hepatocytes, but also in monocytes.…”
Section: Down-regulation Of Cell Surface Gp130 Expression By Inflammamentioning
confidence: 96%
See 1 more Smart Citation